African Continental Free Trade Area Agreement and the Agricultural Performance in Nigeria in the Post Covid-19 Era: A Simulation Focus on Agricultural Output, Trade, and Employment - Akighir, David Terfa; Kpoghul, Emmanuel Tordue (Journal of Developing Economies, 2022)
The COVID-19 pandemic has unleashed negative economic consequences on the global economies and Nigeria inclusive. In response, Nigeria has launched the Economic Sustainability Plan (ESP) to leverage the potential gains of the African Continental Free Trade Area Agreement (AfCFTA) to accelerate agricultural performance in the post-COVID-19 era. Thus, this paper investigated the potential impact of AfCFTA on the performance of the agricultural sector in Nigeria in the post-COVID-19 era focusing on Agricultural output, trade and employment within the framework of a small macro-econometric model. The study used secondary data from 1970 to 2018 for a within-sample forecast and a twelve-year out-of-sample forecast spanning from 2019 to 2030. Two simulation experiments based on AfCFTA tariff reduction lines were conducted. Findings revealed that with tariff reduction under the AfCFTA, there is an increase in agricultural output, exports, employment, and the share of agriculture to GDP growth, as well as actual private consumption in Nigeria. The study concludes that if the AfCFTA is implemented, it will boost agricultural sector performance in Nigeria during the post-COVID-19 era. Based on these findings, the study recommended that the country implement mechanisms to overcome the challenges militating against agricultural production and exports in the economy to maximize the potential gains that AfCFTA provides. The government should also streamline its expenditures and invest hugely in infrastructural facilities such as roads, electricity, and expansion of sea-port facilities, communication networks and earth-dams to encourage dry-season farming activities.